Front Cover: Surface Chemistry of the Molecular Solar Thermal Energy Storage System 2, 3‐Dicyano‐Norbornadiene/Quadricyclane on Ni(111) (ChemPhysChem 16/2022). Issue 16 (18th August 2022) - Hemauer, Felix; Bauer, Udo; Fromm, Lukas; Weiß, Cornelius; Leng, Andreas; Bachmann, Philipp; Düll, Fabian; Steinhauer, Johann; Schwaab, Valentin; Grzonka, Robert; Hirsch, Andreas; Görling, Andreas; et al.
Abstract : The Front Cover shows the concept of molecular solar thermal (MOST) energy storage systems, whereby the light‐harvesting process is combined with storage as molecular strain. The photoinduced isomerization of 2, 3‐dicyano‐norbornadiene to its energy‐rich counterpart is illustrated, after which the backward reaction is catalyzed under energy release. Cover design by Felix Hemauer. More information can be found in the Research Article by Christian Papp and co‐workers .